Electronic gadget use and sleep quality among secondary level students, Kavrepalanchok, Nepal - Waiba, Balaram; Prasad Panta, Prem; Prajapati, Sabisha (Journal of Chitwan Medical College, 2025)
Introduction: Excessive electronic gadget use among adolescents often leads to late bedtimes and poor sleep quality. This study assessed the impact of electronic gadget use on sleep quality among adolescents in a semi-urban town setting in Nepal. Method: A cross-sectional study was conducted among students of grade 12 from 7 schools of Banepa municipality, Kavrepalanchok, Nepal, from 15 to 28 June 2024. A multi-stage cluster sampling technique was used for school and participant selection. Data were collected using self-administered structured questionnaires, including the Pittsburgh Sleep Quality Index (PSQI) and the Digital Addiction Scale Test (DAST) to assess sleep quality and electronic gadget addiction, respectively. Ethical approval was obtained from the Institutional Review Committee of Nobel College (Ref: 080/81/377). Data entry was done in Epi-Data version 3.1 and analysed using SPSS 22. The association between electronic gadget use and sleep quality was determined using Chi-square test, and p<0.05 was considered significant. Result: Out of 288 students, 160(55.6%) were identified as electronic gadget addicts. The majority, 183(63.5%), went to bed after 10:00 PM, and 242(84.0%) reported sleeping less than seven hours per night. Nearly half, 134(46.5%), had poor sleep quality. A significant association was found between late bedtime time (after 10:00 PM) and sleep quality (p=0.047). However, no significant association was found between electronic gadget addiction and poor sleep quality (p=0.279). Conclusion: Students with electronic gadget addiction suffered from poor sleep quality. Students, concerned authorities and guardians should be aware of the adverse effects of excessive electronic gadgets.